Systematic literature review of the use of Staff Attitudes to Coercion Scale (SACS) - Tonje Lossius Husum; Tonje Lossius Husum; Johan Siqveland; Johan Siqveland; Torleif Ruud; Torleif Ruud; Jakub Lickiewicz (Frontiers in Psychiatry, 2023)
ObjectiveStaff’s attitudes to the use of coercion may influence the number of coercive interventions employed and staff willingness to engage in professional development projects aimed at reducing the use of coercion itself. The Staff Attitude to Coercion Scale (SACS) was developed to assess the attitudes of mental healthcare staff to the use of coercion in 2008 and has been employed subsequently. This global study systematically reviews and summarizes the use of the scale in research.MethodsSeven databases were searched for studies using SACS in articles published in peer reviewed journals and gray literature. In addition, researchers who have asked for permission to use the scale since its development in 2008 were contacted and asked for their possible results. Extracting of data from the papers were performed in pairs of the authors.ResultsOf the 82 identified publications, 26 papers with 5,838 respondents were selected for review. A review of the research questions used in the studies showed that the SACS questionnaire was mostly used in studies of interventions aimed at reducing coercion and further explain variation in the use of coercion.ConclusionSACS is, to our best of knowledge, the only questionnaire measuring staff’s attitudes to the use of coercive interventions in mental health services. Its widespread use indicates that the questionnaire is perceived as feasible and useful as well as demonstrating the need for such a tool. However, further research is needed as the relationship between staff attitudes to coercion and the actual use of coercion remains unclear and needs to be further investigated. Staff attitudes to coercion may be a prerequisite for leaders and staff in mental healthcare to engage in service development and quality improvement projects.